Integration of functionality in industrial product design between smart and traditional control (Al-Academy, 2024)
The research tagged (the integration of functionality in industrial product design between smart and traditional control) deals with the study of the impact of digital technologies on industrial products and the process of integration between industrial product systems through the overlap and participation of the function of each system with other systems, it aims to find a comparison in the performance of the industrial product Between smart and traditional control. The limits of the study included the industrial products with traditional control and smart control produced by LG in 2019, and included the theoretical framework, which included three sections, the first of which dealt with the functional performance of the industrial product, while the second topic dealt with the concept of smart and traditional control, and the third topic dealt with the impact of digitization on the integrative functionality.As for the research procedures and methodology, the descriptive approach was adopted in describing and analyzing the sample models. As well as a description and analysis of the sample with its three models according to the analysis axes form that was developed based on what was produced by the indicators of the theoretical framework. The most important results and conclusions that were reached were:1- Digital technologies have achieved their effect on the formal development of the product, as it was achieved by (50%) represented in the models (2,4,6), while it was not achieved by (50%) in the models (1,3,5).2- With regard to welfare, we find that it was achieved by (50%) represented in models (2,4,6), while it was achieved relatively by (16.6%) in Model (1) and was not achieved by (33.3%) in models. (3,5)